Collagen VI and Hyaluronan: The Common Role in Breast Cancer. (13th July 2014) - Karousou, Evgenia; D'Angelo, Maria Luisa; Kouvidi, Katerina; Vigetti, Davide; Viola, Manuela; Nikitovic, Dragana; De Luca, Giancarlo; Passi, Alberto
Abstract : Collagen VI and hyaluronan are widely distributed extracellular matrix macromolecules that play a crucial role in tissue development and are highly expressed in cancers. Both hyaluronan and collagen VI are upregulated in breast cancer, generating a microenvironment that promotes tumour progression and metastasis. A growing number of studies show that these two molecules are involved in inflammation and angiogenesis by recruiting macrophages and endothelial cells, respectively. Additionally, collagen VI induces epithelial-mesenchymal transition that is correlated to increased synthesis of hyaluronan in mammary cells. Hyaluronan has also a specific role in cellular functions that depends mainly on the size of the polymer, whereas the effect of collagen VI in tumour progression may be the result of the intact molecule or the C5 peptide of α 3(VI) chain, known as endotrophin. Collectively, these findings strongly support the parallel role of these molecules in tumour progression and suggest that they may be used as prognostic factors for the breast cancer treatment.